Growth Response of Banana Kepok Tanjung (Musa acuminata balbasiana) with the Application of BAP (Benzyl Amino Purine) and Cow’s Milk In Vitro - Rozanah Indira Lestari; Susiyanti; Samsu Hilal; Andi Apriany Fatmawaty (Faculty of Mathematics and Natural Sciences (FMIPA), Universitas Negeri Padang, Indonesia, 2024)
Tissue culture is a plant propagation technique using artificial media by adding particular growth regulators (ZPT) to produce plants as expected. Although, the availability of other issues such as browning and contamination can inhibit the process of explant propagation. The addition of cow’s milk to the culture media and BAP is a type of cytokinin is expected to regenerate the growth of banan Kepok Tanjung variety optimally. This study aims to have best concentration of BAP and cow’s milk for the growt Kepok Tanjung explants in vitro. The experimental design used was a randomized with 16 treatment combinations. The result showed a significant of the combination of media treatment of banana Kepok Tanjung variety on the number of leaves (24.2 sheets) and explant height (25.62 cm) starting from 3-12 WAP.